Accuracy and validation of a point-of-care blood glucose monitoring system for use in horses - Velineni, Sridhar; Schiltz, Paul; Chang, Ko-Hsin; Peng, Yi-Ming; Cowles, Bobby (Frontiers in Veterinary Science, 2024)
Abnormal blood glucose (BG) levels often seen in critically ill horses are significantly associated with adverse patient outcomes and increased mortality. Rapid and accurate BG monitoring is now considered an essential component of evidence-based equine practice and can provide critical information quickly for treatment. Although several point-of-care (POC) BG monitoring hand-held devices are commercially available for veterinary use, none contains a unique algorithm validated for use in horses. The AlphaTrak 3 (AT3) BG monitoring system is a first-of-its-kind device with an equine-specific algorithm that allows stall-side clinical decision making, and frequent monitoring at minimal cost. As such, AT3 is potentially a preferred alternative to more costly and time-consuming standard diagnostic reference laboratory methods. The objective of this study was to determine the accuracy of the AT3 device in measuring BG levels in equine whole blood samples in comparison to results obtained by the Beckman Coulter AU480 reference analyzer per ISO15197:2013 specifications. Accuracy of the AT3 equine algorithm were initially verified by testing equine blood samples with artificially adjusted blood glucose levels followed by its validation in a field study. Testing with artificially adjusted equine samples (n = 129) showed that 98.9% of glucose measurements ranging from 29 to 479 mg/dL fell within ISO accuracy threshold of ±15 mg/dL or ±15% of the average reference value. In addition, 100% of the AT3 measurements fell in consensus error grid (CEG) zone A, which indicates that test outcomes have a minimal likelihood of adverse clinical impact. In a follow-up field study involving 96 horses, 98.4% of AT3 measurements met the ISO accuracy threshold and 99.2% of AT3 measurements fell in CEG zone A. These results demonstrate that the AT3 glucometer has a high degree of accuracy in horses and is a dependable, convenient, and cost-effective device for accurately monitoring equine BG levels in farm or clinical settings.